Brief Report: Coronary Heart Disease: An Unknown Association to Pathological Gambling - Germain, Candice; Basquin, Anne; Richoux-Benhaim, Charlotte; Embouazza, Houcine; Vahanian, Alec; Lejoyeux, Michel (Frontiers in Psychiatry, 2011)
Pathological gamblers, because of their high level of stress, depression and alcohol or nicotine consumption may be overexposed to coronary heart disease (CHD). To test this association, we assessed pathological gambling (DSM-IV-TR criteria and SOGS scale) among 73 patients hospitalized in cardiology for CHD and 61 in-patients from the same department hospitalized for a non coronary disorder. We found six cases of PG (8.2%) and one case of problem gambling in the CHD group versus no case in the non-coronary group (p=0.01). Pathological gambling was not associated to a higher level of alcohol or nicotine consumption neither to a higher level of sensation-seeking.